Analysis of United States Foreign Policy in Asia Pacific and Its Impact on Regional Security Stability - Widya Setiabudi Sumadinata (International Publisher, 2023)
Interactions between countries in the Asia Pacific region have a direct bearing on the way in which security in that region evolves through time. Recent events have elevated the bilateral relationship between China and the United States to the status of an intriguing phenomena, largely due to the fast growth of China's economy and military. Because of this scenario, the emphasis of United States political policy, which had previously been placed on the Middle East region, has shifted to the Asia Pacific region. The presence of two countries, each of which is striving to achieve domination in the Pacific, will have an effect on the safety of the surrounding area. Therefore, the purpose of this article will be to attempt to study the political policies of the United States in the Asia Pacific region and to determine what influence such policies have on the stability of regional security. area that was implemented by China through the OBOR in order to compete with the United States as a major power in the Asia Pacific region and ended up perceiving the US rebalancing strategy as a response to China's domination in the Asia Pacific region.